Personalizable Alternative Mouse and Keyboard Interface for People with Motor Disabilities of Neuromuscular Origin - Andreas, Daniel; Six, Hannah; Bliek, Adna; Beckerle, Philipp (ASSETS 2022 - Proceedings of the 24th International ACM SIGACCESS Conference on Computers and Accessibility, 2022)
People with motor disabilities of neuromuscular origin often struggle with operating the computer through a commercially available mouse and QWERTY keyboard. This work presents an alternative mouse and keyboard interface, which is personalizable to meet the individual needs of the target population to allow a more efficient use of the computer. The regular/commercially available mouse is therefor replaced by a spectacle frame equipped with pressure sensors for mouse click activation and an inertial measurement unit for mouse cursor control through head movements. The alternative keyboard is based around a ten button keyboard, with multiple letters assigned to each key. The users can then chose the desired word from a list of word suggestions that is compiled based on the keyboard input. Prior experiments, the users went through a software guided calibration procedure to experimentally determine individual thresholds and parameters. The system was tested by two nondisabled participants through typing and click tests, followed by a questionnaire to give feedback on the system.
CRIS-Team Scopus Importer:2022-11-18
Keywords: alternative input device; assistive technology; Fitts' law; human-computer interaction; neuromuscular disease; personalization